2019
DOI: 10.1080/10942912.2019.1628778
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of four polysaccharides containing β-D-Glu p on intestinal function

Abstract: Plant polysaccharides exert a wide range of biological effects on the intestinal function. In this study, four polysaccharides containing β-D-Glup, including Dendrobium officinale polysaccharide (DOP), Dendrobium aphyllum polysaccharide (DAP), and glucans from yeast (G-Y) and barley (G-B), were investigated in vitro for their intestinal-promoting functions such as inhibition of digestive enzymes, effect of blood glucose and blood lipid levels by using ultraviolet spectrophotometry, as well as the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Furthermore, enzyme activity was decreased in concentration depending-manner. The obtained results were in agreement with several works reported in the literature with regards to the anti-protease effects of polysaccharides 42,43 .…”
Section: Anti-protease Activity Of Plp1supporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, enzyme activity was decreased in concentration depending-manner. The obtained results were in agreement with several works reported in the literature with regards to the anti-protease effects of polysaccharides 42,43 .…”
Section: Anti-protease Activity Of Plp1supporting
confidence: 92%
“…It was reported that there was a relationship between polysaccharide viscosity, protease activity 43 and reduction of protein digestibility 44 . Therefore, there may be multiple mechanisms by which polysaccharides affect protease activity.…”
Section: Anti-protease Activity Of Plp1mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipase activity was totally inhibited at 2.5 mg and 3.0 mg/mL. These results are similar to those found by [39]. The antioxidant activity of polysaccharide from plant extracts have received an extensive study and attention.…”
Section: Inhibitory Effects On Lipasesupporting
confidence: 88%
“…The inhibitory capacities of the polysaccharide on pancreatic lipase were evaluated [18]. Briefly, various concentrations of the polysaccharide solution (0.5, 0.75, 1.0, 1.5, 2.0, 2.5, 3.0 mg/L, 1.0 mL), soybean oil as a substrate (1.0 mL), 5 mL phosphate buffer solution (0.1 mol/L, pH 7.2) and 1 mL of lipase solution (0.71 mg/mL, pig pancreatic Type II) were combined and incubated at 37°C for 1 h. The mixture was transferred to a boiling water bath for 5 min and then centrifuged (4800 g, 10 min) (L600, Cence Test Instrument Co., Ltd., Hunan, China).…”
Section: Determination Of Bioactive Activities Of Astragalus Spinosis Polysaccharide 241 Anti-lipase Activity Of Plasmentioning
confidence: 99%